2009
DOI: 10.1080/02699930802121137
|View full text |Cite
|
Sign up to set email alerts
|

Memory for emotional faces in major depression following judgement of physical facial characteristics at encoding

Abstract: The aim of the present study was to establish if patients with major depression (MD) exhibit a memory bias for sad faces, relative to happy and neutral, when the affective element of the faces is not explicitly processed at encoding. To this end, 16 psychiatric outpatients with MD and 18 healthy, never-depressed controls (HC) were presented with a series of emotional faces and were required to identify the gender of the individuals featured in the photographs. Participants were subsequently given a recognition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…Thus, as the participants in Deveney and Deldin's study were Short-term memory for faces in dysphoria 5 not required to overtly process the emotional content of the faces, a MCM bias would not have been expected. Consistent with this notion, Ridout et al. (2009) reported that clinically depressed patients did not exhibit a bias for sad faces following a nonemotional encoding task (gender identification).…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Thus, as the participants in Deveney and Deldin's study were Short-term memory for faces in dysphoria 5 not required to overtly process the emotional content of the faces, a MCM bias would not have been expected. Consistent with this notion, Ridout et al. (2009) reported that clinically depressed patients did not exhibit a bias for sad faces following a nonemotional encoding task (gender identification).…”
Section: Introductionmentioning
confidence: 62%
“…It is well known that depression and dysphoria are associated with impaired social functioning (Gotlib & Lee, 1989;Harkness, Sabbagh, Jacobson, Chowdrey & Chen, 2005;Joiner & Coyne, 1999;Petty, Sachs-Ericsson & Joiner, 2004). It has been suggested that alterations in face processing may contribute to, or even account for, impaired social functioning in depression (Persad & Polivy, 1993;Ridout et al, 2009). In line with this notion, the memory bias for sad and angry faces observed in depressed individuals could plausibly impact negatively on their social functioning.…”
Section: Introductionmentioning
confidence: 93%
“…Because cognitive sché-mas are thought to have limited conscious accessibility, the current collection of studies examining explicit memory retrieval represents only a partial empirical exploration of cognitive theories. Preliminary results suggest that explicit processing may be necessary for explicit recognition memory biases to emerge (e.g., Gilboa-Scbechtman et al, 2002;Ridout et al, 2003;Ridout, Dritschel, et al, 2(X)9). However, it will be important for future research to examine depressive implicit memory for relevant facial affect following explicit encoding of affect.…”
Section: Depressed Samplementioning
confidence: 93%
“…A long-term memory bias for sad faces has been found in patients with depression (Gilboa-Schechtman, Erhard-Weiss, & Jeczemien, 2002;Ridout, Astell, Reid, Glen, & O'Carroll, 2003), in individuals experiencing dysphoria (Jermann et al, 2008;Ridout, Noreen, & Johal, 2009), and in individuals in an induced sad mood (Ridout, Dritschel, et al, 2009). A short-term memory bias for sad faces has been found in patients with melancholic depression (Linden, Jackson, Subramanian, Healy, & Linden, 2011), but not in individuals with subclinical dysphoria (Noreen & Ridout, 2010).…”
Section: Discussionmentioning
confidence: 91%